The Academic as Public Intellectual: Examining Public Engagement in the Professionalised Academy. (December 2015) - Dallyn, Sam; Marinetto, Mike; Cederström, Carl
In this article we critically consider the widely held conception that the public intellectual is in decline. We present a more sanguine fate of this figure, arguing that today we observe a flourishing of intellectuals. One such figure is the academic intellectual who has often been looked at with suspicion as a technical specialist. This conception suggests that university intellectuals are diluted versions of the historical conception of the 'true' public intellectual – that is, an 'independent spirit' that fearlessly challenges unjust power. In this article, we contest this view, arguing that this historical conception, idealised as it may be, nevertheless can inform scholastic activities. By resituating the public intellectual as a kind of temperament rather than a title, we examine its pressing – but at the same time uneasy – relevance to contemporary academic life. Counterposing this with contemporary instrumental conceptions of research impact, we suggest that where possible the intellectual academic should aspire to go beyond academic institutional norms and requirements. Hence, the academic public intellectual refers to a temperament, which is in but not of the academic profession.